Embedded automation in human-agent environment - Tweedale, Jeffrey W. (Adaptation, Learning, and Optimization, 2012)
This research book proposes a general conceptual framework for the development of automation in human-agents environments that will allow human- agent teams to work effectively and efficiently. We examine various schemes to implement artificial intelligence techniques in agents.  The text is directed to the scientists, application engineers, professors and students of all disciplines, interested in the agency methodology and applications.